Histomorphometric analysis of stomach walls alternation under conditions of general body dehydration. - Hula, V. I.; Sikora, V. Z. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Changes of the composition of food and beverages intake by modern humans do not fulfill the nutritious, energetic and water needs of the body. This causes rapid growth of gastrointestinal diseases. The stomach is particularly susceptible to the influence of external factors. Water-salt metabolism disorders cause structural and functional alternations of the stomach as one of the digestive organs. Objective. The present study was conducted to identify changes of the fundus of the stomach wall of the rats under condition of general body dehydration of different severity level. Methods. The object of this research was a group of 29 adult white male laboratory rats with average weight of 150-170 g. The control group comprised of 7 rats which had the usual water intake in the course of the experiment. Light dehydration occurred on the 3rd day of the experiment, medium dehydration happened on the 6th day and severe dehydration – on the 9th day. The animals were sacrificed on the days stated above by means of euthanasia with anesthetic ethers. Sampling and fixation were carried out in accordance with the established procedures. To examine the structural components the histologic sections were stained with hematoxylin and eosin stain, using Van Gieson's staining and Mallory staining. Morphometric analysis included defining of the thickness of stomach walls of the animals of all the groups. Results. On the 3rd day from the experiment launch (mild dehydration) there was observed a fair decrease in the average layer thickness of the surface epithelium as well as other components of the stomach walls as compared to the results of the intact group of animals. Mallory staining determined a major thinning of the mucous layer on the surface of the gastric mucosa as well as mucus presence in cytoplasm of mucous cells. On the 6th day of the experiment (moderate dehydration) the average layer thickness of surface epithelium decreased compared to the control group. There was a tendency of thinning of the stomach wall thickness and all of its structural components as compared to the intact animal group. Mucous membrane had erosions which looked like surface defects on the gastric folds. On the 9th day of the monitoring (severe dehydration) a considerable decrease of thickness index of all of the gastric wall components. This was accompanied by irreversible dystrophic and necrobiotic cell changes mainly in the gastric glands necks and bodies which lead to total cytolysis. There is reported moderate vascular blood congestion, haemorheologic disorders which manifest themselves as stasis and thrombosis of microcirculatory bloodstream vessels. Conclusion. The obtained results indicate thinning of stomach walls, irreversible dystrophic changes and partial loss of gland cells function as well as local circulation failure and haemorheologic changes in microvascular vessels which progress from mild to severe general dehydration.